Revitalisasi Kecakapan Literasi Informasi Pustakawan Sekolah Melalui Pelatihan Operator GScholar Advanced Search - Windah Andi; Purwanto Putra; Arnila Purnamayanti; Eri Maryani (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: School librarians, although proficient in various search engines, often face challenges in effectively accessing and utilizing resources, particularly the members of the Lampung Province Indonesian School Library Staff Association (Asosiasi Tenaga Perpustakaan Sekolah Indonesia/ATPUSI). The core aim of this project is to enhance the efficient and productive use of global technology. Methodology: Google Scholar (GScholar) Advanced Search Operators Technology Training was introduced as a community service activity to boost ATPUSI members’ information literacy skills. This involved active participation in Focus Group Discussions and offering instructional resources on how to use Google Scholar technology effectively. The service was executed in July 2023, incorporating teaching methods, such as lectures, question-response interactions, and specific evaluation methodologies. To gauge the comprehension level, an evaluation was conducted using pre-set questionnaires in both pre-test and post-test formats. Results: The outcome of this service shows an improvement in the perception and efficiency of school librarians regarding the use of advanced search operators for information retrieval. In addition, there seems to be increased awareness and understanding of the significance of precise information in promoting the growth of information literacy skills among beneficiaries. Limitations: The training was tailored for ATPUSI members; therefore, generalizing the results to other school librarians or regions requires caution. Additionally, unmentioned factors such as librarians' technological infrastructure, prior experience with similar tools, and ongoing professional development could have affected the outcomes. Contributions: Community services improved the information literacy skills of ATPUSI members. This outcome is important because it shows the progress in information literacy in education. The training program equips librarians with access to and leverage reliable information sources effectively.